Communicative-visual value of environmental art festival - Antonella Violano; Julio Cesar Perez-Hernandez (Agathón, 2018)
Many forms of art leave their imprint on contemporary art culture as a complex system of ideas and emotions, perceptions and stimuli for reflection. The role of artistic installations in historical contexts is related to the impermanence between necessity and pleasure, showing how works of art become a necessity not only for the artist but above all for the urban spaces that welcome them and for the people who live there. The socio-cultural value of this kind of event is part of the cathartic and pedagogical role of art, which allows urban spaces to find ideas for enhancement and people to experience the emotion of belonging. The considerations contained in the contribution are the result of many years of scientific collaboration between the two authors on the issues of the relationship between art and architecture, and deepen two strongly representative cases: the biennial Festival of Environmental Art Seminar Sogninterra in Maranola and the Havana Art Biennale.